Pengaruh Audit Tenure, Financial Distress dan Opini Going Concern Terhadap Auditor Switching Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Naibaho, Mega Amelia Lamtiar; Anggriyani; Hidayat, Taufik (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to prove the effect of audit tenure, financial distress and going-concern opinion variables on auditor switching in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research is a type of causal research, which uses population data from 182 manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period. The sampling method used was a purposive sampling method and obtained data that passed the test as many as 53 sample companies and 159 observations. The data used are secondary data in the form of annual reports and audited financial statements of each sample company published on the website www.idx.co.id. The data analysis technique used is descriptive statistics and logistic regression analysis with SPSS 25 software. The conclusion of this study is that audit tenure has a negative and significant effect on auditor switching, financial distress has a negative and insignificant effect on auditor switching, and going concern opinion has a positive and significant effect on auditor switching